OSBPL10, a novel candidate gene for high triglyceride trait in dyslipidemic Finnish subjects, regulates cellular lipid metabolism - Perttilä, Julia; Merikanto, Krista; Naukkarinen, Jussi; Surakka, Ida; Martin, Nicolas W.; Tanhuanpää, Kimmo; Grimard, Vinciane; Taskinen, Marja-Riitta; Thiele, Christoph; Salomaa, Veikko; Jula, Antti; Perola, Markus; et al. (Journal of molecular medicine (Berlin, Germany), 2009)
Analysis of variants in three genes encoding oxysterol-binding protein (OSBP) homologues ( OSBPL2 , OSBPL9 , OSBPL10 ) in Finnish families with familial low high-density lipoprotein (HDL) levels ( N = 426) or familial combined hyperlipidemia ( N = 684) revealed suggestive linkage of OSBPL10 single-nucleotide polymorphisms (SNPs) with extreme end high triglyceride (TG; >90th percentile) trait. Prompted by this initial finding, we carried out association analysis in a metabolic syndrome subcohort (Genmets) of Health2000 examination survey ( N = 2,138), revealing association of multiple OSBPL10 SNPs with high serum TG levels (>95th percentile). To investigate whether OSBPL10 could be the gene underlying the observed linkage and association, we carried out functional experiments in the human hepatoma cell line Huh7. Silencing of OSBPL10 increased the incorporation of [ 3 H]acetate into cholesterol and both [ 3 H]acetate and [ 3 H]oleate into triglycerides and enhanced the accumulation of secreted apolipoprotein B100 in growth medium, suggesting that the encoded protein ORP10 suppresses hepatic lipogenesis and very-low-density lipoprotein production. ORP10 was shown to associate dynamically with microtubules, consistent with its involvement in intracellular transport or organelle positioning. The data introduces OSBPL10 as a gene whose variation may contribute to high triglyceride levels in dyslipidemic Finnish subjects and provides evidence for ORP10 as a regulator of cellular lipid metabolism.